EFEKTIFITAS PEMBERIAN MAKANAN TAMBAHAN (PMT) TERHADAP PENURUNAN STUNTING DI KOTA PAYAKUMBUH - Neldi, Elfira; Muharja, Fajri (Ensiklopedia of Journal, 2024)
Stunting is still a health problem in Indonesia, one of the interventions carried out is by Providing Additional Food (PMT). PMT is the provision of additional food to meet the nutritional needs of toddlers. This study aims to assess the effectiveness of PMT in reducing the incidence of stunting and identifying factors that influence the incidence of stunting. Knowing the implementation of government policies and programs related to PMT in Payakumbuh City and proposing improvements or enhancements to be more effective in reducing stunting. The design used in the study was quantitative descriptive with data analysis techniques using the Limited Dependent Variable class with a Logistic Regression model. The population in this study were toddlers who experienced stunting in Payakumbuh City in 2023 who received PMT assistance. The sampling technique was purposive sampling. The results of the study illustrate that the incidence of stunting is significantly influenced by the number of PMT and the family's economic level with p values of 0.031 and 0.018 (<5%). The variables of parental education, medical history, complete basic immunization status, and environmental sanitation have not had a significant effect on reducing stunting, this can be seen from the results of the regression p value greater than 5%. It is recommended that when providing PMT, parents are equipped with knowledge of the benefits and methods of administration and increase monitoring so that PMT is more effective in reducing stunting.Key words: Effectiveness, Stunting, supplementary feeding